Proteomics and phosphoproteomics of freshwater mollusk carcasses reveal novel insights as potential food source - Liu, Gongzhen; Wang, Shengkang; Wang, Tielin; Zhu, Changan; Li, Changlong; Zhang, Xinyi (Frontiers in Cellular and Infection Microbiology, 2025)
Cipangopaludina chinensis, Radix auricularia, and Nodularia douglasiae are common freshwater mollusks widely distributed in lakes and rivers across China. In this study, (DIA) Data - independent acquisition method was used to analyze the proteomics and phosphoproteomics among three species. The results showed that a total of 1,382 proteins were identified from mollusk carcasses, with 492 proteins were quantitively analyzed. These proteins are mainly involved in amino acid nutrition and metabolism, including glutamate dehydrogenase, glyceraldehyde-3-phosphate dehydrogenase, and tyrosinase copper-binding domain-containing protein. Bioinformatics analysis revealed that the identified proteins are primarily involved in carbon metabolism, microbial metabolism, ubiquitin-mediated proteolysis, and RAS signaling pathways. Notably, this study offers valuable insights into the differential protein expression of proteins across species. Furthermore, proteomics analysis revealed several novel proteins, which helps to improve our understanding of amino acid metabolism, protein diversity, and signaling pathways in these freshwater mollusks.